Vienna Phiharmonic Concert, January 27, 1901, conducted by Gustav Mahler - Wiener Philharmoniker::::::::::::::: (v; Austria; Verlag der Philharmonischen Concert-Unternehmung, 2020)
Program for a performance by the Vienna Philharmonic with Gustav Mahler conducting Beethoven's Ninth Symphony, op. 125, with, text printed on verso.